Environmental changes recorded in the sequence of lake-peat bogs in the Eemian Interglacial and Vistulian on the basis of multi-proxy data. (20th September 2022) - Mirosław-Grabowska, Joanna; Borówka, Ryszard Krzysztof; Radzikowska, Magdalena; Sławińska, Joanna; Hrynowiecka, Anna; Sobczyk, Artur; Stachowicz-Rybka, Renata; Stefaniak, Krzysztof
Abstract: We present the results of geochemical investigations, including stable isotope, of the Eemian (MIS 5e) and Vistulian (Weichselian, MIS 5a–d, MIS 3–4) sediments of the palaeolake horizons from Gorzów Wielkopolski site (NW Poland). Our analyzes comprised two profiles from different parts of lake basin, each approximately 11-m long. The deposits represent two cycles of lake accumulation (two limnic layers), each ended by peat deposition, separated by mineral fluvial deposits. The lower and upper limnic layers, despite several similar geochemical features, are records of two separate phases of the lake's functioning. The palynological data suggest that the mineral deposits separating them are not continuous succession, but contain a stratigraphic hiatus. We characterized six geochemical zones (GZ), which correspond well with lithological features of deposits and climatic changes, and reflect the changing environmental conditions (redox conditions, variability and intensity of denudation, biological productivity, and fertility of the environment). In the first phase of lake's development, some influence of the surface material supply is visible, indicated by the increased content of lithophilous elements, (e.g. potassium), as well as closely correlated with them copper and zinc. Slow accumulation of carbonates dominated the limnic layers due to their abundant supply from the catchment area. The greatest variations of isotopic values of carbonates occur in the bottom and at the top of the stratigraphic profile and are related to the changing environmental conditions in the lake's basin (water level and temperature variations). The differences in carbon and nitrogen isotope values suggest different sources of organic matter accumulated in the studied basin and varying trophy of the environment. The higher mercury content is related to the course of climate change and is the highest in cold periods. We identified five main phases of evolution of the palaeolake at Gorzów Wielkopolski site. The lake accumulation began during the final phase of the Wartanian (Late Saalian) Glaciation (MIS 6). Initially the palaeolake harmonically developed and reached its maximum depth (Early and Middle Eemian, MIS 5e). Next the palaeolake became shallower and transformed into the peatbog (Late Eemian, MIS 5e). In the Early Vistulian period (or Early Weichselian, MIS 5a–d), the lake re-existed, initially as a flow-through lake. Finally in middle Vistulian (or Middle Weichselian – Pleniglacial, MIS 3–4), the palaeolake declined and mire developed.